IMPLEMENTASI ETIKA BISNIS ISLAM DALAM JUAL BELI ONLINE - Rizkiani, Rizkiani (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2022)
In people's lives, business is something that is quite significant. First of all, in the 21st century. in the flow of telephones which was coupled with the outbreak of the covid-19 disease which previously hit this country, so that this increased the influence of the community in doing business both selling and buying. The modern business world is no longer rigid and many have even implemented spirituality in business, even new spiritual discoveries are widely adopted and applied as standard operating procedures in the workplace. The purpose of this research is to show how Islamic business ethics can be applied to online buying and selling while educating readers about the importance of following Islamic business ethics. Library research is a series of tasks related to collecting data from the library, reading and taking notes, and organizing research materials in this study. The principles of Islamic online business ethics, which include the principles of divinity, morality, balance, individual freedom, fairness, and benefit, honesty, and legitimacy, must be followed by sellers in online buying and selling transactions. This is because one of the main objectives of these principles is to enforce customer rights.